Framing Analysis of Hajj Departure Cancellation Policy During the Covid-19 Pandemic - Mutiara Yusdhiana; Sri Hastjarjo; Sudarmo (Formosa Journal of Social Sciences (FJSS), 2022)
The Covid-19 pandemic has raised concerns due of its impact on different aspects of society, particularly religious life. Apart from the very high risk of international pilgrims returning home with the COVID-19 virus, the growing number of cases in Saudi Arabia will add to the already overburdened health-care system in Mecca and Medina. The aim of the research is to examine at how the Hajj Departure Cancellation Policy was portrayed during the COVID-19 Pandemic. This research employs a qualitative descriptive method with the purpose of presenting reported cases in a systematic, honest, and accurate manner. The research data was obtained from various reports that appeared on the online news portal, including CNBC Indonesia, Kompas.com, VoA Indonesia. The study's results indicate that the framing analysis on the three online media websites CNBC Indonesia, Kompas.com, and VoA Indonesia resulted in the construction of the reality of the hajj cancellation policy by defining the problem, namely the Covid-19 pandemic, which caused the Saudi Arabian government to not yet invite Indonesian pilgrims and open hajj services in 1442 H/2021 M. Most importantly, the Indonesian government is attempting to protect its citizens from the spread of Covid-19